Pengaruh Layanan Purna Jual Dan Variasi Produk Terhadap Keputusan Pembelian Laptop Asus: Studi Kasus Pada Pelanggan Pegasus Computer Tebing Tinggi - Ade Mubarak; Sinaga, Eka Mayastika; Dio Landika Pratama (Management And Business Progress, 2022)
This study aims to find out how the influence of after-sales service and product variety on purchasing decisions for Asus laptops. The research method uses multiple linear regression analysis. The results of the hypothesis test state that: Hypothesis 1 is rejected, so after-sales service has no effect on purchasing decisions. Hypothesis 2 is accepted, so Product Variation influences Asus Laptop Purchase Decisions. Hypothesis 3 is accepted, then After-Sales Service and Product Variety have a joint effect on Asus Laptop Purchase Decisions. This research is a replication of previous research where the difference lies only in the object studied.